2020
DOI: 10.3390/ijerph17113850
|View full text |Cite
|
Sign up to set email alerts
|

N-Fertilizer (Urea) Enhances the Phytoextraction of Cadmium through Solanum nigrum L.

Abstract: Heavy metal contamination is currently a major environmental concern, as most agricultural land is being polluted from municipal discharge. Among various other pollutants, cadmium (Cd), one of the most harmful heavy metals, enters into the food chain through the irrigation of crops with an industrial effluent. In the present study, a pot experiment was designed to assess the effect of different nitrogen (N)-fertilizer forms in the phytoremediation of Cd through Solanum nigrum L. Two types of N fertilizers (NH4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 52 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…An increase in the number of publications from 2011 to 2021, with an anticipated increase in the number in 2022, shows that the research on biochar compost is still growing and is being explored by researchers from different fields of study, and countries or regions. The increasing attention can be explained by the effect of steady and continuous application of inorganic fertilizers on plant accumulation of heavy metals, decreasing grain quality and nutrition of crops [ 104 ; 105 ], including water, air, and soil pollution through the accumulation of toxic chemicals in water bodies, and physical soil degradation [ 106 ]. Contrary to the long-term application of inorganic fertilizers, biochar-based compost has proven to be an effective organic fertilizer for soil heavy metal immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of publications from 2011 to 2021, with an anticipated increase in the number in 2022, shows that the research on biochar compost is still growing and is being explored by researchers from different fields of study, and countries or regions. The increasing attention can be explained by the effect of steady and continuous application of inorganic fertilizers on plant accumulation of heavy metals, decreasing grain quality and nutrition of crops [ 104 ; 105 ], including water, air, and soil pollution through the accumulation of toxic chemicals in water bodies, and physical soil degradation [ 106 ]. Contrary to the long-term application of inorganic fertilizers, biochar-based compost has proven to be an effective organic fertilizer for soil heavy metal immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Total and available P concentrations were 2.20 mg kg −1 and Zn, Cu, Cd total and available concentrations were 0.81 mg kg −1 ; 0.34 mg kg −1 and 0.09 mg kg −1 , respectively. Complete physicochemical characteristics of the soil used in this experiment are described before (Arosha et al, 2020) [ 22 ]. This experiment had been carried out in botanical garden of Government College University Faisalabad (Faisalabad, Pakistan; 31°25′0″ N 73°5′28″ E) during (April–June) in 2019.…”
Section: Methodsmentioning
confidence: 99%
“…NO 3 supplementation might increase organic acid production and promote Cd translocation via xylem through organic acid complex forms [142]. Several other studies also revealed that N fertilizer in the form of NH 4 + in soil increased Cd uptake via rhizospheric acidification and root cell proton excretion in sunflower and S. nigrum plants [138,143]. Moreover, Xie, et al [144] found that supplementation with NO 3 − promotes Cd and Zn phytoextraction by Noccaea (Thlaspi) caerulescens.…”
Section: Nitrogenmentioning
confidence: 97%